FRI0515 Quantification and Impact of Secondary Osteoarthritis in Patients with Anti-Citrullinated Protein Antibodies Positive Rheumatoid Arthritis. (15th July 2016) - Figueiredo, C.P.; Simon, D.; Englbrecht, M.; Haschka, J.; Kleyer, A.; Bayat, S.; Hueber, A.J.; Pereira, R.M.; Rech, J.; Schett, G.
Abstract : Background: Erosions have been described as the hallmark of bone damage in RA, resembling catabolic changes [1]. Usually bone erosions in RA are not accompanied by proliferative bone changes, which are typically found in psoriatic arthritis and spondyloarthritis [2]. Although such changes are much less pronounced in RA than in other diseases, RA patients may not be completely spared from bony proliferations, which likely resemble the development of secondary osteoarthritis. Objectives: To search for evidence of secondary osteoarthritis in patients with rheumatoid arthritis (RA) in a cross-sectional and longitudinal setting and to relate osteophyte formation to functional outcome. Methods: Anti-citrullinated protein antibody positive (ACPA+) RA patients underwent high-resolution peripheral quantitative computed tomography (HR-pQCT) of the hand. Cross-sectional and longitudinal measurements were performed. Number and size of osteophytes as well as bone erosions were documented. Relation of osteophytes to bone erosions and to demographic and disease specific data was evaluated by multiple logistic regression models. Results: 202 ACPA+ RA patients were enrolled in the cross-sectional and 77 subjects in the longitudinal analysis (interval: 1.5 years). The mean number and size of osteophytes was 1.3±2.3 and 9.4±23.9 mm 3 respectively. Osteophyte number was significantly (p<0.001) correlated to erosion number and osteophyte size to erosion size (p<0.001). Moreover, presence and size of osteophytes were related to age (p<0.001), disease duration (p<0.001) and health assessment questionnaire (HAQ) (p=0.013). Multivariate regression analyses showed an independent association between osteophytes and erosions. In the longitudinal analysis the mean number (p=0.033) and size (p<0.001) of osteophytes significantly increased in RA patients during their disease course (Figure 1 ). Conclusions: Age, disease duration and bone erosions are associated with osteophytes indicating development of secondary osteoarthritis in patients with RA. References: McInnes IB, Schett G. The pathogenesis of rheumatoid arthritis. N Engl J Med. 2011;365(23):2205–19. Diarra D, Stolina M, Polzer K, Zwerina J, Ominsky MS, Dwyer D, et al. Dickkopf-1 is a master regulator of joint remodeling. Nat Med. 2007;13(2):156–63. Disclosure of Interest: None declared